Islamic Feminism and Online Communities: Exploring Women's Empowerment in Indonesia - Zebua, Dinny Rahmayani; Khatibah, Khatibah (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
The use of social media has significantly increased, transforming from being perceived as a cause of educational problems to an important tool for sharing knowledge and experiences. Consequently, online communities such as Perempuanmasadepan.id on Instagram have emerged as platforms for women's empowerment, offering a space for individuals to support each other and expand social networks. The purpose of this study is to analyze the implementation of women's empowerment programs carried out by the online community Perempuanmasadepan.id on Instagram and to become a benchmark for further research on whether empowerment can be implemented through online communities. This research uses a descriptive qualitative approach to analyze various facts and arrive at a conclusion. The data collection techniques used by the researchers included observation, documentation, and interviews. The data analysis used uses narrative data analysis techniques. Researchers refined the results of interviews with informants, namely, the founder of womenmasadepan.id and three members with different work backgrounds in the womenmasadepan.id community. This study found that the implementation of women's empowerment programs through online communities saves time, improves relationships, and builds women's confidence in social media and their environment.